A utilização de material didático impresso para o ensino de um modelo de classificação do esporte na educação física escolar - Barroso, André Luís Ruggiero [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study was related to the sport classification system, using internal logic as a reference, based on the criteria of cooperation, interaction with the opponent, comparative performance and tactical objectives of the action, using printed educational material - teacher's notebook and student's notebook. Thus, the aim of the study was to investigate which are the relevant changes that should be made by physical education teachers, working in the eighth and/or ninth grade regarding the educational material, to teach the sport classification system, developed by the Rio Grande do Sul Department of State Education, according to the existing teaching needs, and whether these changes address other groups of teachers who work at the same level of education. Using the action research method, this study had the effective participation of seven teachers, who were divided into two groups: A - developed the lessons with original educational material and B - used the teaching materials modified by the members of the first group. The results were organized into three categories for discussion: understanding and assessment of the sport classification system, understanding and assessment of educational material, implementation of the educational material related to the sport classification system. In the first category, favorable factors related to teaching of the classification system were observed, mainly emphasizing better presentation, organization and structuring of content and the diversity of the sports that were taught. Regarding the second category, initially the teachers showed insecurities and fears, mainly due to not having experience in dealing with the educational material, however, after using the material, they emphasized that it can be an important teaching tool, which helps the pedagogical process, as long as the teacher is allowed to make changes in accordance to their educational realities. As for the third category, a big part of...

A pesquisa tratou do ensino do sistema de classificação do esporte, tendo como referência a lógica interna, com base nos critérios de cooperação, de interação com o adversário, do desempenho comparado e dos objetivos táticos da ação, a partir da utilização de um material didático impresso - caderno do professor e caderno do aluno. Desta forma, o objetivo do estudo foi investigar quais as mudanças pertinentes a serem realizadas pelos professores de Educação Física atuantes no oitavo e/ou nono anos do Ensino Fundamental em relação ao material didático, para o ensino do sistema de classificação do esporte, elaborado pela Secretaria de Educação do Estado do Rio Grande do Sul, de acordo com as necessidades presentes em suas práticas pedagógicas, e se essas alterações atendem a outro grupo de professores que atuam no mesmo nível de ensino. Utilizando o método da pesquisa-ação contou com a participação efetiva de sete professores, divididos em dois grupos: A - desenvolveu as aulas com o material didático original e B - utilizou o material didático modificado pelos integrantes do primeiro grupo. Os resultados foram organizados em três categorias de discussão: compreensão e avaliação do sistema de classificação do esporte, compreensão e avaliação do material didático, implementação do material didático referente ao sistema de classificação do esporte. Na primeira categoria foram observados fatores favoráveis ao ensino do sistema de classificação, destacando-se principalmente uma melhor apresentação, organização e estruturação do conteúdo e a diversidade de modalidades esportivas contempladas. Em relação à segunda categoria, inicialmente os professores demonstraram inseguranças e receios, principalmente pelo fato de não terem experiência no trato com material didático, entretanto, após a sua utilização, ressaltaram que este pode se apresentar como um importante instrumento de...
Keywords: Physical education and training - Study and teaching; Educação física - Estudo e ensino; Material didático; Esportes; Livros didáticos; Ensino - Curriculos